Inhibition of Integrin αvβ3-FAK-MAPK signaling constrains the invasion of T-ALL cells - Lan Huang; Yao Zhu; Qinglin Kong; Xianmin Guan; Xiaoying Lei; Luying Zhang; Hui Yang; Xinyuan Yao; Shaoyan Liang; Xizhou An; Jie Yu (Cell Adhesion & Migration, 2023)
ABSTRACTThe role of adhesion receptor integrin αvβ3 in T-ALL was unclear. Firstly, we performed quantitative real-time PCR to assess medullary expression of integrin β3(ITGB3) in T-ALL patients and high ITGB3 expression was relevant with the central nervous system leukemia(CNSL) incidence. Decreasing of cell invasion was observed in Jurkat and Molt4 treated with integrin αvβ3 specific antibody and inhibitor as well as cells with ITGB3 interference. Further, phosphorylation of FAK, cRAF, MEK and ERK decreased in cells with integrin αvβ3 inhibition or interference. Invasion decreased in T-ALL cells treated with FAK and ERK inhibitors. In conclusion, inhibition of integrin αvβ3 signals significantly limits the cell invasion of T-ALL cells.